Analisis Faktor–Faktor yang Mempengaruhi Penghasilan Karyawan Wanita di PT Pal Indonesia Kota Surabaya Pada Tahun 2017–2021 - Gobay, Daniel A; Yustie, Renta (Economie: Jurnal Ilmu Ekonomi, 2023)
This research is entitled "Analysis of the Factors Affecting the Earnings of Women Workers at PT Pal Indonesia from 2017 to 2021 in the City of Surabaya". The purpose of this study was to measure and analyze whether the level of education of women (X1), tenure of female employees (X2) and the number of female employees (X3) partially and simultaneously have a significant effect on the income of female employees (Y) at PT Pal Indonesia, Surabaya city. From a total of 65 observations, a sample of 13 divisions was used in this study. This research uses literature study and documentation study to collect data. The multiple linear regression model, or OLS, is the analytic approach used in this study. The results of the data analysis show that the variables of female education level (X1), female employee tenure (X2) and number of female employees have a partial and simultaneous significant effect on the variables income of female employees (Y). Other results show that the contribution or contribution of the Education Level of Women (TPW), Years of Service of Female Employees (MKW) and Number of Female Employees (JKW) together have an influence on the Income of Female Employees (PKW), which is equal to 60.2380%. While the remaining 39.7620% is caused by other factors not examined in this study.